Continuous Flow Supercritical Chemical Fluid Deposition of Optoelectronic Quality CdS - Yang, Jixin; Hyde, Jason R.; Wilson, James W.; Mallik, Kanad; Sazio, Pier J.; O'Brien, Paul; Malik, Mohamed A.; Afzaal, Mohammad; Nguyen, Chinh Q.; George, Michael W.; Howdle, Steven M.; Smith, David C. (Advanced materials (Weinheim), 2009)
Supercritical chemical fluid deposition (SCFD) has been shown to have remarkable advantages for deposition inside nanostructured templates however so far the technique has mostly been used to deposit metals. In this paper we present the SCFD of optoelectronic grade CdS. The quality of this material is demonstrated by a range of techniques including reflectivity (A) and photoluminescence spectroscopy (B and C). At 4 K the bandedge luminescence has a full‐width‐at‐half‐maximum linewidth of 30 meV comparable with that of single crystal CdS.